Taxonomic study of the genus Oxyethira Eaton 1873 (Trichoptera: Hydroptilidae) from Northeast Brazil: Eleven new species and distributional records - Souza, Wagner Rafael M. De; Santos, Allan Paulo Moreira (Zootaxa, 2017)
The genus Oxyethira comprises over 200 species distributed worldwide. In Brazil, 23 species have been recorded, mostly from the North Region, but this number is still an underestimate. To date, six species have been recorded from the Northeast Region of Brazil (from Ceará, Piauí, and Pernambuco states). In this work, we describe and illustrate 11 new species from this region: Oxyethira calori sp. nov., O. diplospissa sp. nov., O. guariba sp. nov., O. iannuzzae sp. nov., O. maranhensis sp. nov., O. rafaeli sp. nov., O. gracilianoi sp. nov., O. retrosa sp. nov., O. septentrionalis sp. nov., O. singularis sp. nov., O. una sp. nov. Additionally, new distributional records for five other species are given. These results increase the number of Oxyethira species in Brazil from 23 to 35.